Initial Identification of Mudharabah Savings Market Share Improvement Strategies in Indonesia - Putri Ramadhani Saragih; Jaenal Effendi; Imam Teguh Saptono (Indonesian Journal of Business and Entrepreneurship (IJBE), 2018)
Sharia banking has been arising for 26 years in Indonesia. Its market share is still lower than 5%. Study about sharia banking’s market share is always an interesting observation. Mudharabah savings as one of the third party fund has a significant role to improve market share by low cost fund type. The objectives of this study are to analyze mudharabah savings elasticity, significant independent factor to it and initial market share improvement strategies. The methods used to combine vector error correction model (VECM) and business model canvas (BMC). This research concludes that conventional bank rates and sharia bank outlets have a relationship with mudharabah contract savings demand. Furthermore, mudharabah savings has a substitute relationship with conventional saving by negative cross elasticity. The results are combined with business model canvas (BMC) to describe mudharabah saving business model as a managerial action to explain initial strategies of mudharabah saving. BMC arranged by choosing conventional bank rates as value proposition focus and sharia bank outlets as key resources focus.Keywords: demand elasticity, mudharabah savings, business model canvas (BMC), sharia banking, initial strategies